Internal Labor Mobility in Central Europe and the Baltic Region - Paci, Pierella; Tiongson, Erwin R.; Walewski, Mateusz; Liwinski, Jacek; Stoilkova, Maria M. (Washington, DC : World Bank, 2012)
Drawing from a variety of data sources and utilizing a common empirical framework and estimation strategy, this study identifies patterns and statistical profiles of geographical mobility. It finds internal migration to be generally low and highly concentrated among better-educated, young, and single workers. This suggests that migration is more likely to reinforce existing inequalities than to act as an equalizing phenomenon. By way of contrast, commuting flows have grown over time and are more responsive to regional economic differentials. The findings suggest the need for appropriate and country-tailored policy measures designed to increase the responsiveness of labor flows to market conditions.